Antiwashout behavior of calcium phosphate cement incorporated with Poly(ethylene glycol) - Hablee S.; Sopyan I.; Mel M.; Salleh H.M.; Rahman M.M. (Institute of Physics Publishing, 2023)
Calcium; Calcium phosphate; Cements; Compressive strength; Ethylene glycol; Hydrated lime; Hydroxyapatite; Lime; Liquids; Manufacture; Polyethylene glycols; Polyols; Precipitation (chemical); As-synthesized powder; Calcium phosphate cement; Di-ammonium hydrogen phosphate; Distilled water; Hydroxyapatite powder; Powder to liquid ratio; Ringer's solution; Wet-chemical precipitation; Strength of materials